Expediting Marriage Dispensation: Balancing Child's Best Interests with Expediency Principle - Sucia, Andi Tenri; Patittingi, Farida; Marwah (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2023)
This study analyzes the application of the expediency principle in the Marriage Dispensation Decision in relation to the Principle of the Best Interest of the Child. Using an empirical legal research approach, the study gathers primary data from Pangkajene and Barru Religious Courts (Class II), Maros Religious Court (Class 1B), Makassar Religious Court (Class 1A), Barru District Court (Class II), and Makassar District Court (Class 1A Special). Descriptive qualitative analysis of the data reveals that the application of the expediency principle is linked to the Best Interest of the Child principle in the Pangkajene and Barru Religious Courts. However, there is room for improvement as judges often overlook important information regarding the child's background, needs, and problems, resulting in suboptimal cooperation across sectors for preventing underage marriage. In contrast, the Maros and Makassar Religious Courts have effectively balanced the child's best interests and expediency, leading to a decline in underage marriages. These courts prioritize the child's best interests and consider the law to ensure the child's well-being and continuity of life. The findings highlight the challenges and opportunities for improving the application of the expediency principle in Marriage Dispensation, ultimately benefiting the protection and welfare of children involved.